Evaluation of Driver Behavior to Hydroplaning in the State of Florida Using Driving Simulation - Villiers, Claude; Guo, Dahai (Universitas Indonesia, 2019)
This project used a driving simulator to investigate patterns of drivers’ behavior during rainfall events using different geometries. We conducted a literature review of previous transportation studies using driving simulators and selected and analyzed extensive field data on major highway sections throughout Florida. The driving simulator at the University of Central Florida simulated the parameters such as speed and rainfall intensity observed in the field.Based on our analysis, we found that drivers are not affected by light rainfall events. However, heavy rainfall has a significant impact on their speed; on average they reduced their speed by 6 to 12 mph. Also, there is no interaction between rainfall intensity and either gender or age group. The female participants appeared to drive faster as compared to their male counterparts and the age group ranging from 16 to 21 year olds to be the most aggressive drivers. Eighty percent (80%) of the participants reported on the survey that they have experienced some level of hydroplaning while driving on the road. The simulator appears to provide identical results to the field data analysis, lending credence to the validity of using a driving simulator to investigate the pattern of drivers’ behavior during rainfall events.The researchers recommend further validation and refinement of this study. Continuation of this project may also help Florida Department of Transportation and other agencies with future decision making, such as Variable Message Signs, determining appropriate corrective measures on existing roadway sections, and/or designing future roadway sections to reduce hydroplaning.